2010
DOI: 10.1143/jpsjs.79sa.133
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Effects of Silver Ions on Forming Cooperative Conduction Path in Superionic Melts

Abstract: In Ag-based superionic melts, medium-range order in the Ag-Ag partial correlation relating to the fast ionic conducting path of Ag ions was analyzed as a function of Ag concentration. High energy x-ray diffraction measurements for molten Ag 2 Se and (Ag 2 Se) x (AgI) 1-x mixtures and (RbI) y (AgI) 1-y were carried out. In molten (Ag 2 Se) x (AgI) 1-x mixtures, a first sharp diffraction peak (FSDP) is not observed in the total structure factor for x = 0.2 and 0.3. On the other hand, molten (RbI) y (AgI) 1-y mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Structural investigation of molten (RbCl) c (AgCl) 1-c and (RbI) c (AgI) 1-c mixtures, especially reduction of Ag-Ag partial correlations is indispensable to complete full discussion on transport properties in relation with unusual flat Ag-Ag pdf of molten AgCl and anomalous Ag migration in molten AgI. We have already measured the structure of molten (RbI) c (AgI) 1-c mixtures [28] and we plan to measure the structure of molten (RbCl) c (AgCl) 1-c mixtures. We will discuss the relation between transport properties and the partial structures in a near future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural investigation of molten (RbCl) c (AgCl) 1-c and (RbI) c (AgI) 1-c mixtures, especially reduction of Ag-Ag partial correlations is indispensable to complete full discussion on transport properties in relation with unusual flat Ag-Ag pdf of molten AgCl and anomalous Ag migration in molten AgI. We have already measured the structure of molten (RbI) c (AgI) 1-c mixtures [28] and we plan to measure the structure of molten (RbCl) c (AgCl) 1-c mixtures. We will discuss the relation between transport properties and the partial structures in a near future.…”
Section: Discussionmentioning
confidence: 99%
“…The (RbI) c (AgI) 1-c mixtures has stoichiometric compound RbAg 4 I 5 which shows the superionic phase even at room temperature [23][24][25][26][27], and its structure factor at molten phase has the largest scale of medium-range order in the molten (RbI) c (AgI) 1-c system [28]. We have two motivations in this study.…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that the Ag distribution in Ag 0,5 (GeSe 3 ) 0.5 has a tendency of forming chain-like fragments even in the molten state, which is characteristic feature in the Ag based superionic melts such as AgI [4] and Ag 2 Se [5]. The grown-up of medium-range order with decreasing temperature is related to the process of Ag ionic conduction path formation in the molten and supercooled liquid states [3].…”
Section: Introductionmentioning
confidence: 97%
“…Figure 2 shows the behavior conductivity and its abrupt jump in conductivity using Equation (7) and the probability distribution function (5). The fits are good because the carriers follow a temperature-dependent probability distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Superionic conductors allow the movement of ions through their structure, showing unusually high ionic conductivity values (similar to liquid electrolytes). Silver iodide or AgI, since its high conductivity was discovery in 1914 [1] has been extensively studied from both experimentally [2][3][4][5][6] and theoretically [7][8][9][10][11][12][13] points of view. At atmospheric pressure, AgI is polymorphic [14] with phases denoted by γ, β, and α, accessible with increasing temperature T. At room temperature, the γ phase [15] is thermodynamically meta-stable with a zinc blende structure and the β phase [16] is stable with a wurtzite structure.…”
Section: Introductionmentioning
confidence: 99%